Interference fit effect on holed single plates loaded with tension-tension stresses - D. Croccolo; M. De Agostinis; N. Vincenzi (Fracture and Structural Integrity)
This paper deals with the influence of interference fit coupling on the fatigue strength of holed plates. The effect was investigated both experimentally and numerically. Axial fatigue tests have been carried out on holed specimens made of high performance steel (1075MPa of Ultimate strength and 990MPa of Yield strength) with or without a pin, made of the same material, press fitted into their central hole. Three different conditions have been investigated: free hole specimens, specimens with 0.6% of nominal specific interference and specimens with 2% of nominal specific interference. The experimental stress-life (S–N) curves pointed out an increased fatigue life of the interference fit specimens compared with the free hole ones. The numericalinvestigation was performed in order to analyse the stress fields by applying an elastic plastic 2D simulation witha commercial Finite Element software. The stress history and distribution along the contact interference of the fitted samples indicates a significant reduction of the local stress range due to the externally applied loading (remote stress) since a residual and compressive stress field is generated by the pin insertion.